Murdoch mysteries. Season 07 [videorecording (DVD)] - Bisson, Yannick, 1969-; Bisson, Yannick, 1969-; Harris, Jonny; Craig, Tom, 1962-; Jennings, Maureen (Distributed by RLJ Entertainment, 2014)
"Detective William Murdoch ... solves the most perplexing mysteries of Edwardian-era Toronto with scientific insight and revolutionary techniques"--Container.